Children’s Handicaps in Online Learning: A Highlight on Learning Applications - Tarpan Suparman (STAI Hubbulwathan Duri, 2022)
This current study aims to document the challenges encountered by children in adapting to the learning applications in online learning. A literature study is used to answer the research question. The data was obtained from a systematic search in the Google scholar. From the search, 23 articles from 2000 – 2021 were gathered as the research data. To analyze the data, a content analysis was implemented. The findings revealed that the children met the difficulties because they tend to have short concentration span and the limitation of learning device and signal stability. Moreover, less parents’ control causes young learners disoriented while using the applications. Surprisingly, the students did not face hindrance in relation to the applications use. Most of them adapted quite easily in using the applications. This implies that children nowadays are very adaptive towards technology and are easier to learn through diverse platforms in online learning. Limitations and future recommendations are also presented.